Lone Star State of Mind - King, Jaime; 1979- (Culver City, Calif., 2003)
With a couple of grand in the bank and a dream in their heart, Earl and Baby plan their escape from their hometown in Bennett, Texas. They are heading to Los Angeles. But Earls dim-witted cousin, an ex-con and an angry drug lord are threatening to derail their plans. With just 48 hours to straighten out this mess, Earl finds himself smack dab in the middle of an even bigger mess.
Keywords: Receiving stolen goods; Drama; Man-woman relationships; Texas; Drama; Texas; Description and travel; Drama